THE LEVEL OF SERVICE QUALITY OF FAST-FOOD RESTAURANTS IN SEMARANG - Imam Nuryanto; Ida Farida (Jurnal Penelitian Ekonomi dan Bisnis, 2020)
The purpose of this research is to find out the influence of service quality (tangible, reliability, responsiveness, empathy) on customer loyalty. The object chosen in this research is fast-food restaurant in Semarang. The sample in this research is determined by purposive sampling method which then obtained the number of a sample as many as 100 respondents. The data in this research were obtained by the questionnaire. The data analysis used in this research is multiple linear regression analysis methods. The results of this research prove and give the conclusion that: service quality has a positive and significant influence on customer loyalty. The empathy variable is the highest variable affecting customer loyalty, because during the COVID 19, personal service was needed. Each consumer is unique, so the needs of customer services vary. Customers can use delivery or take away, home delivery, drive-thru, online and KFC box servicesKeywords: service quality; customer loyalty; fast-food restaurant